A genetic analysis of the occurrence of pulmonary haemorrhage in racing thoroughbreds in Southern Africa - Weideman, Heinrich (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD(Agric))--University of Stellenbosch, 2004.